Effectiveness of Disc Excision in the Treatment of Herniated Lumbar Intervertebral Disc - Amir, Sohail; Qadir, Maimoona; Usman, Muhammad (Journal of Gandhara Medical and Dental Science, 2017)
OBJECTIVE To determine the efficacy of disc excision in the treatment of herniated lumbar intervertebral disc. METHODOLOGY This study was conducted at Neurosurgery Department of Naseer Teaching Hospital, Peshawar from February 2015 to January 2016.The study design was descriptive case series in which consecutive non probability sampling technique was used. Clinical outcome of patients undergoing discectomy was determined using Stauffer-Coventry criteria and patients rated as excellent, good, fair and poor RESULT A total of 88 patients were recruited with 64% males and 36% females. Mean age was 39 years+4.68 SD.70% patients had L4-L5 and 30% had L5-S1 level disc herniation. Laminectomy was performed in 58%,fenestration in 34% and hemilaminectomy in 8% patients. Postoperatively at four weeks, satisfactory pain relief reported by 85% and unsatisfactory pain relief reported by 15% patients. CONCLUSION Conventional laminactomy, fenestration or hemilaminectomy is a feasible, safe and effective treatment in patients with lumbar disc herniation. Relief of pain is faster for patients assigned to early surgery.